SCHOOL HEAD INNOVATION IN IMPROVING DAYA COMPETITION IN SMP MUHAMMADIYAH 1 KLATEN - Istanto, Istanto; Nur Jannah, Ernani (Muhammadiyah University Press, 2019)
This research aims to describe the Principal's innovation in increasing competitiveness in SMP Muhammadiyah 1 Klaten and describe the implementation of School Principals' innovation in increasing competitiveness in SMP Muhammadiyah 1 Klaten in the academic year 2019 / 2020. The type of research the researchers conducted was field research. with a qualitative - descriptive approach. Namely research that describes and analyzes events, social activities, attitudes, thoughts of individuals individually or in groups. The data collection technique used by researchers is in three stages. Observation, interview and documentation stages in order to get accurate information. In this study the source of data obtained by snowballing include Principals, Teachers, Students and Staff Staff. As a result of this determination, there were a number of school principals' innovations in improving competitiveness at SMP Muhammadiyah 1 Klaten. Among other innovations carried out are: (1) Developing a Full day class program with three choices. (2) The Extracurricular Program as a support in fostering students in a Full Day three-choice class. (3) Developing the 2013 curriculum, SBC and curriculum from the school. Innovations improve school competitiveness are also supported by improvements in facilities and infrastructure in the teaching and learning process. This three day full day program was initiated to carry out the vision that was created by the school to instill religious based character education (Islam and based on the needs of the community. In improving the school's competitiveness, the teachers also included workshops to understand and practice curricula that were in accordance with the government.